ANALISIS GAYA BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA KELAS III SD DHUHAA ISLAMIC SCHOOL KOTA TANGERANG - Septianti, Nabillah; Boy Dorahman; Aam Amaliyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Based on the background of the problem, it was found that the learning styles of class III students at SD Dhuhaa Islamic School varied. Not the same as one another. There are those who learn with a learning style of paying attention to the teacher's explanation (visual), there are those who learn by listening to the teacher carefully (auditory), but there are also students who move a lot and cannot sit still for a long time (kinesthetic), even though the lesson is in progress. .The aims of this research are: 1) To describe the visual learning style, auditory learning style and kinesthetic learning style of class III SD Dhuhaa Islamic School students 2) To find out the learning methods used by class III teachers at Dhuhaa Islamic School Elementary School when learning with the learning styles of students who use combination of VAK learning styles. This research is a qualitative descriptive study with the research subjects being three class III students at SD Dhuhaa Islamic School. Data collection techniques in the form of questionnaires, tests and in-depth interviews were used to obtain data on student learning style analysis and document study. The results of this research show that class III students at SD DhuhaaIslamic School learn using a combination of learning styles (VAK). With a tendency towards one learning style.